Descriptive review of geographic mapping of severe acute respiratory syndrome (SARS) on the Internet - Boulos, Maged N Kamel (BioMed Central, 2004)
From geographic mapping at different scales to location-based alerting services, geoinformatics plays an important role in the study and control of global outbreaks like severe acute respiratory syndrome (SARS). This paper reviews several geographic mapping efforts of SARS on the Internet that employ a variety of techniques like choropleth rendering, graduated circles, graduated pie charts, buffering, overlay analysis and animation. The aim of these mapping services is to educate the public (especially travellers to potentially at-risk areas) and assist public health authorities in analysing the spatial and temporal trends and patterns of SARS and in assessing/revising current control measures.